The effects of thin mud deposits on the behaviour of a deposit-feeding tellinid bivalve: implications for ecosystem functioning. Issue 4 (4th July 2017) - McCartain, Lisa D.; Townsend, Michael; Thrush, Simon F.; Wethey, David S.; Woodin, Sarah A.; Volkenborn, Nils; Pilditch, Conrad A.
ABSTRACT: A laboratory experiment was conducted, to examine how feeding, siphon activity and movement behaviours of a tellinid bivalve, Macomona liliana (Iredale, 1915), were affected by thin surface layers of mud (1–4 mm) and the incorporation of mud into surface (0–2 cm) sediment. Time-lapse photography and porewater pressure sensors were used to characterise changes in behaviour before and after mud addition. Mud addition modified the sediment matrix which had an immediate effect on M. liliana behaviour; significantly affecting the rates of feeding and the degree of porewater pressurisation during feeding events. Surface activity indicated maintenance and clearance of established burrow structures and increased ventilation. Ultimately, subtle modifications in behaviour and sediment hydraulic conductivity may have consequences for nutrient exchange and benthic-pelagic coupling. Our results emphasise the need to consider the impacts of low level stressors when they affect the behaviour of structurally important species.